INTERPRETATION OF LARGE-SCALE MORPHODYNAMIC LABORATORY EXPERIMENTS: SPOIL HEAPS AND SANDBANKS - Garcia-Hermosa, M; Borthwick, A; Soulsby, R; Stansby, P; Taylor, P; Huang, J; Zhou, J (2009)
A series of tests has been undertaken on the morphodynamic evolution of sand mounds in unidirectional steady and oscillatory tidal flows generated in the U.K. Coastal Research Facility. The sand mounds are qualitatively representative of spoil heaps or sandbanks in coastal or estuarine waters. A detailed dataset has been established of bed changes with respect to the ambient flow conditions that should be useful for validating numerical models used for the prediction of large-scale coastal morphodynamic processes. The influence of various parameters on integral properties of the evolving sand mound is considered, encompassing variations in the flow conditions, initial shape of mound, initial height of mound, and underlying bed conditions (i.e. whether fixed or mobile). The results of tests involving coloured sand are discussed. A comparison is made of the experimental measurements of migration and lateral spread of the mound in unidirectional flow with an analytical solution derived by De Vriend (1987). © 2009 World Scientific Publishing Co. Pte. Ltd.